A Combined AHP-GP for Maintenance Project Selection in Coal Power Plant - Hery Setiyawan; Udisubakti Ciptomulyono (IPTEK Journal of Proceedings Series, 2020)
A proper maintenance project selection is a key to support performance of power plant. The issue of maintenance is allocation a limited budget to achieve the goals of various maintenance criteria and conflicting objectives. This paper presents an integrated AHP and goal programming. In the first step, since maintenance is measured in qualitative criteria, it is recommended to use AHP to weight and quantify criteria. Second step utilize GP which uses the criteria weights and alternative priorities calculated with AHP to optimize multiple objectives without exceeding available resource constraint. The results show that the approach can aid in selection optimal projects within available budget.